2002
DOI: 10.4269/ajtmh.2002.66.422
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of eastern equine encephalitis virus and West Nile virus from crows during increased arbovirus surveillance in Connecticut, 2000.

Abstract: Abstract. The emergence of the West Nile virus (WNV) in the northeastern United States has drawn emphasis to the need for expanded arbovirus surveillance in Connecticut. Although the state of Connecticut began a comprehensive mosquito-screening program in 1997, only since 1999 have there been efforts to determine the prevalence of arboviruses in bird populations in this state. Herein, we report on our results of an arbovirus survey of 1,704 bird brains. Included in this report are the first known isolations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The SmartCycler protocol for the detection of West Nile virus in use at the DPH Laboratory for the testing of bird brains uses 2.5 l of extract (3). Initial studies in the DPH Laboratory with influenza A virus indicated that 2.5 l yielded the best results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The SmartCycler protocol for the detection of West Nile virus in use at the DPH Laboratory for the testing of bird brains uses 2.5 l of extract (3). Initial studies in the DPH Laboratory with influenza A virus indicated that 2.5 l yielded the best results (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing important roles in expanding geographical distribution of EEEV, bird hosts are also necessary for the amplification of NA EEEV [8]. High attack and fatality rates are commonly associated with EEEV infection of horses, but has also been documented in swine [9], pheasants [10], ostriches [11], emus [12], turkeys [13] and whooping cranes [14].…”
Section: Introductionmentioning
confidence: 99%
“…To detect viral activity in subsequent years, surveillance programs were implemented through out the United States (Beckwith et al, 2002;Cherry et al, 2001;Komar, 2001). Spread of the WNV is likely to further continue till an endemic infection level is established in the continent.…”
Section: Introductionmentioning
confidence: 99%
“…WNV in birds has been shown to be a systemic disease showing multiple organ involvement (Steele et al, 2000). Diagnosis of WNV in birds has mostly relied upon identifying the presence of virus in the bird tissues, using virus isolation and or real-time RT-PCR (Beckwith et al, 2002). A monoclonal antibody based enzyme immunosorbent assay that distinguishes WNV from other flaviviruses has now also become available (Hunt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%